The Synergetic Effect of Lithium Bisoxalatodifluorophosphate and Fluoroethylene Carbonate on Dendrite Suppression for Fast Charging Lithium Metal Batteries - Shi, Pengcheng; Liu, Fanfan; Feng, YueZhan; Zhou, Jiafeng; Rui, Xianhong; Yu, Yan (Small (Weinheim an der Bergstrasse, Germany), 2020)
Fluorinated solid‐electrolyte interphase (SEI) derived from fluoroethylene carbonate (FEC) is particularly favored for dendrite suppression in lithium metal batteries because of the high Young's modulus (≈64.9 Gpa) and low electronic conductivity (10−31 S cm−1) of LiF. However, the transportation ability of Li+ in this fluorinated SEI under high current densities is limited by the low ionic conductivity of LiF (≈10−12 S cm−1). Herein, by rational design, 0.1 m lithium bisoxalatodifluorophosphate (LiDFBOP) is adopted to modify fluorinated SEI in FEC based electrolyte for fast charging lithium metal batteries. Benefiting from the synergetic effect of LiDFBOP and FEC, a fluorinated SEI rich in LiF and LixPOyFz species can be yielded, which can further improve the stability and ionic conductivity of SEI for fast Li+ transportation. Meanwhile, the average coulombic efficiency for Li plating/stripping is improved from 92.0% to 96.7%, thus promoting stable cycling of Li||Li symmetrical batteries with dendrite free morphologies, even at high current densities (3.0 mA cm−2) and high plating/stripping capacities (3.0 mAh cm−2). More attractively, in practical Li||LiNi0.6Co0.2Mn0.2O2 batteries, the cycling life at 1C and rate capacities at 6C are also significantly improved. Therefore, the synergetic effect of LiDFBOP and FEC provides great potential for achieving advanced lithium metal batteries with fast charging ability. Lithium bisoxalatodifluorophosphate (LiDFBOP) is proposed to modify fluorinated solid electrolyte interphase (SEI) in fluoroethylene carbonate based electrolyte for fast charging lithium metal batteries. With 0.1 m LiDFBOP, the stability and ionic conductivity of SEI layer for fast Li+ transportation is improved. Thus enabling stable cycling of Li||Li batteries with dendrite free morphologies, even at 3 mA cm−2, 3 mAh cm−2.